2018
DOI: 10.18632/aging.101394
|View full text |Cite|
|
Sign up to set email alerts
|

CD40L promotes development of acute aortic dissection via induction of inflammation and impairment of endothelial cell function

Abstract: Acute aortic dissection is one of the most lethal cardiovascular disease. The major histopathological feature of AAD is medial degradation, especially breakdown of elastin and collagen. However, the underlying mechanism remains a mystery. Platelets expressed CD40 Ligand (CD40L) is recently recognised as a key effector of cardiovascular disease development through its pro-inflammatory effect. To clarify the role of CD40L in AAD, we examined level of CD40L in human blood serum samples and found that it is signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 43 publications
(56 reference statements)
1
21
0
1
Order By: Relevance
“…Moreover, suppression of EC apoptosis induces inflammation in aorta 47 . ECs dysfunction promotes AD development through pro-inflammatory effect 14. VSMC dysfunction can be stimulated by endothelial injury signals, and participates in the pathogenesis of vascular diseases 49.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, suppression of EC apoptosis induces inflammation in aorta 47 . ECs dysfunction promotes AD development through pro-inflammatory effect 14. VSMC dysfunction can be stimulated by endothelial injury signals, and participates in the pathogenesis of vascular diseases 49.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of previous studies related to the pathogenesis of AD has been on VSMCs 12-13. Although some studies have found abnormal appearance of ECs in AD 14-15, the role of ECs in the pathogenesis of AD remains largely unknown. However, endothelial dysfunction is predictive of vascular events and long-term clinical outcome 16-18.…”
Section: Introductionmentioning
confidence: 99%
“…They are important in regulating blood flow, and thus, are involved in numerous physiological processes (6). Inflammation can result in VEC dysfunction and further promote AD progression (7). Angiotensin II (Ang II) is the major effector peptide of the renin-angiotensin system (RAS), which induces vasoconstriction, hypertrophy and extracellular remodeling via the angiotensin type 1 receptor (AT1R) (8).…”
Section: Introductionmentioning
confidence: 99%
“…AD is a disease in which the structure of the aortic wall is degraded, eventually causing the intima to rupture, with blood entering the media to form a FL (Han et al, 2018). Macrophages respond mainly to Ang II, and the recruitment, activity and secretion of macrophages in the aortic wall trigger and maintain inflammation there (Dimmeler et al, 1997;Daugherty et al, 2000;Schluter and Wenzel, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological surveys have shown that the incidence of thoracic AD is 3-4 per 100,000 individuals per year (Olsson et al, 2006;Kochanek et al, 2011). AD is defined as blood flow that enters the aortic media through intimal tears, followed by formation of a true lumen (TL) and a false lumen (FL) with or without communication (Han et al, 2018). Computed tomography angiography (CTA) images of normal aorta and AD in patients from our center are shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%